Credit facility for horticultural sector in India – An empirical study - ROY, TUHIN NARAYAN; ROY, PINAKI (The Indian Journal of Agricultural Sciences, 2022)
Working with the secondary sources of empirical data (2009–10 to 2018–19), the present study tries to show the status of agricultural credit facility with special reference to horticultural sector in India. Tabular analysis with simple compound annual growth rate (CAGR) has been done in 2020. In case of crop loan (short-term credit), agriculture and horticulture have no difference and the system of delivery is also similar. Horticulture finance includes loans for development of fruit orchard, poly-house, green house development and marketing of such produce. Agricultural credit is vital in India for 86.2% small and marginal farmers for capital formation. Financial support in horticulture was lacking. Productivity credit inter alia as evinced in term of growth rates of area (CAGR=1.56%), production (CAGR=2.72%) and productivity (CAGR=1.28%) shows better performances compared to agriculture. But fund allotment in government (govt.) budget for horticulture remains almost constant (CAGR=0.86%). Study suggested for more investment (public and private) in horticulture since it contributes 29.2% of agricultural GDP and provides nutritional security. Popularization of microcredit, farmers’ awareness and improve technologies for delivery of institutional loan can be ensured. Diversion of crop loan must be checked. Study also highlights different govt. schemes for overall development of the horticulture sector.